RELIGIOUS EDUCATION IN THE TRADITION OF WALIMAH AL-SAFAR AMONG LEIHITU INDIGENOUS PEOPLE IN CENTRAL MALUKU: A STUDY ON THE SYMBOLIC INTERACTION ON WALIMAH AL-SAFAR - Abdullah Latuapo (Erudio Journal of Educational Innovation, 2022)
This study aims to explain the values of religious education in walimah al-safar in Leihitu. For a long time, the tradition has only been seen from the social-ritual and sociological aspects, even though this tradition is also full of religious and educational values, especially Islamic values. This research used a qualitative field approach or field research. This research was conducted in Leihitu, Central Maluku Regency, to investigate the social and symbolic interactions between the Leihitu people in the ritual practice of walimah al-safar. The results are as follows. First, walimatal-safar is carried out in 3 forms: before the prospective hajj goes to Mecca, while in Mecca, and after returning from Mecca. This ritual involves kumpul basudara” followed by a pilgrimage to the graveyard, reading Maulid Barzanji, reading Surah Yasin and Manaqib, and tausiyah or preaching—all of which is held to forgive each other. People also eat together, give charity, and respect all guests. Second, walimatal-safar is full of universal religious values, including affection, sincerity, honesty, unity, cooperation, and equality. Of these values, the most dominant affecting the daily social interactions of the Leihitu people are compassion, unity, cooperation, and nationality.